The relevant market in competition law: a legal concept. (11th March 2019) - Robertson, Viktoria H S E
Abstract: In competition law, the relevant market acts as a filter that delineates that part of commerce within which competition law assesses companies' market behaviour. This contribution considers how competition law can reconcile the legal concept of the relevant market with its economic roots. It argues that for market definition—like for many an economic concept—a spectrum opens up between law and economics. On the economics side of the spectrum, economics may take on a more determinative role almost amounting to normative force. This places considerable pressure on the integrity of economics. On the law side of the spectrum, the relevant market is looked at through the prism of the law and is seen as a legal concept building upon an economic one. Here, economics is assigned an interpretive role. A plethora of different positions are possible along the spectrum, and different actors may place themselves at different locations under different circumstances or at different points in time. If it is acknowledged that the relevant market concept acquires a distinct legal conception through its incorporation into the competition laws, then this has far-reaching repercussions on our entire conception of competition law. This view effectively calls into question not only competition law's understanding of the relevant market, but also the prevailing understanding of other shared legal and economic concepts.